The Effectiveness of Group Therapy on Rescuing Patients with Cancer - Hossein Malekzadeh Fini; Hassan Heydari; Seyyed Ali Al Yassin (Ital Publication, 2017)
Recent studies show that the cancer has several negative results. The anxiety, depression and disappointment are more common than the others. Hopefully thinking and cancer in two ways are related together. First the hopeful people use The problem-focused coping strategies more than the others and show less anxious and more agreement to diagnosis and treatment of cancer. So the goal of this survey is the effect of group hope therapy on reciliency of cancer patients. In this survey the Quasi-experiment and pre-test and pro test with control group is used. The society are all of the cancer patients who are coming to Kashan Imam Hassan institution and 16 of them are chose by available sampling and randomly put in two trial and control group. The trial group participated in nine group consultation sessions and the control group had no education. For toleration testing the Conroy Davidson questionnaire 2003 is used. Data are analysed by co variance analysis. The results show that the group hope therapy had a meaning full effect on toleration and the idea of personal competency, negative affection tolerance and acceptation of positive changing and spiritual control and affection s are affected the scales. Hope let people to have no stress and enable them to try to reach to their goals, the hope therapy try to enable people to have a view beyond the current situation and pain and suffering. So the toleration is not more than tolerance of the difficult situations and every things that make better the situation of cancer patients will increase the toreciliency.